2017
DOI: 10.1038/srep45981
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide identification and functional prediction of cold and/or drought-responsive lncRNAs in cassava

Abstract: Cold and drought stresses seriously affect cassava (Manihot esculenta) plant growth and yield. Recently, long noncoding RNAs (lncRNAs) have emerged as key regulators of diverse cellular processes in mammals and plants. To date, no systematic screening of lncRNAs under abiotic stress and their regulatory roles in cassava has been reported. In this study, we present the first reference catalog of 682 high-confidence lncRNAs based on analysis of strand-specific RNA-seq data from cassava shoot apices and young lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(158 citation statements)
references
References 63 publications
(92 reference statements)
7
150
1
Order By: Relevance
“…Among 24,368 lncRNAs, 983 and 1288 were responsive to cold treatment in the leaves and roots. The cold-responsive lncRNAs found in our study are more than those identified in cassava, and this may result from the different sequencing methods and plant species, such as different genome sizes and sensitivities to low temperature stress [44].…”
Section: Discussionmentioning
confidence: 71%
“…Among 24,368 lncRNAs, 983 and 1288 were responsive to cold treatment in the leaves and roots. The cold-responsive lncRNAs found in our study are more than those identified in cassava, and this may result from the different sequencing methods and plant species, such as different genome sizes and sensitivities to low temperature stress [44].…”
Section: Discussionmentioning
confidence: 71%
“…As previously described (Li et al, 2017), A total of 140 gigabase in-depth sequencing of library was performed initially on a HiSeq 2500 instrument that generated paired-end reads with 125 nucleotides. After filter out the adapter and low quality sequences, TopHat2 (Trapnell et al, 2012) was used to map the clean reads to cassava genome.…”
Section: Methodsmentioning
confidence: 99%
“…With advances in next-generation sequencing technology, many investigations have shown that lncRNAs exert their regulatory effects on gene expression levels, including epigenetic regulation, transcriptional regulation, and post-transcriptional regulation in the form of RNA [19]. It is known that sequence-specific DNA binding transcription factor activity [42,58], response to stimulus [59], response to abiotic stimulus [58], biosynthetic process [58], structural constituent of ribosome [56], photosynthesis [60] and oxidoreductase activity [60], which are regulated by some lncRNAs, have been reported in response to abiotic stresses, and these GO terms were identified in this study. To determine the similarity and differences between the two genotypes, the significantly enriched GO terms were compared.…”
Section: Differentially Expressed Lncrnas Specifically Enriched In Gomentioning
confidence: 99%
“…We found that phosphoprotein phosphatase activity, protein metabolic process, and sequence-specific DNA binding were significantly and specially enriched in Q2, while single-organism metabolic process, photosynthesis, and oxidoreductase activity were significantly and specially enriched in Qinyou8. Additionally, lncRNAs have been recognized as powerful regulators of pathways in response to drought stress, including ribosome, photosynthesis [61], and plant hormone signal transduction [42,62]. The ribosome pathway was simultaneously significant in both genotypes, and the differential lncRNA target genes were up-regulated in this pathway.…”
Section: Differentially Expressed Lncrnas Specifically Enriched In Gomentioning
confidence: 99%
See 1 more Smart Citation